Sugar Intake Risks and Benefits and the Global Diabetes Epidemic - James Martins, Ian (IntechOpen, 2021)
Rates of diabetes are increasing worldwide with cases spreading to various regions of both developing and developed countries, increasing the risk of various organ diseases. Nutritional interventions such as low-calorie, low-sugar diets have now become critical for combatting the disease. Written by experts from around the globe, this book examines the risks and benefits of sugar intake and the critical role of functional foods in treating diabetes. The chapters provide information to control sugar intake and to prevent the induction of organ disease in diabetic individuals.